Effects of enzyme maceration on physicochemical properties and micronutrient bioaccessibility of Strychnos cocculoides products (juice/porridge) - Nyoni, Qhubekani (Midlands State University, 2017)
Information on the nutritional content and health-promoting properties of African indigenous fruits is very limited. Although the limited available literature does point towards wealth in essential nutrients, micronutrients and antioxidants there is still a need to fill the gap to ascertain health and nutritional claims that have been passed on from previous generations. Studies on the impact of processing of the fruit pulp on physicochemical, nutritional properties, and digestibility thereof are still very scarce and fragmented. Hence, the focus of this study was to explore enzyme (pectinase) maceration as a processing option to enhance physicochemical properties, antioxidant activity, antimicrobial potential and bioaccessibility of selected micronutrients in Strychnos cocculoides (S, cocculoides) juice/pulp. In this context, enzyme maceration refers to the breakdown of pectin that occurs in fruit pulp as complex structural polysaccharides into simpler, soluble compounds by the action of a commercial mixture of pectinases. Enzyme maceration has been reported to be beneficial in improving juice yield and enhances release of bioactive compounds into resultant juice from fruit pulps. Since the juice is commonly consumed with maize-meal porridge, the S. cocculoides enriched porridge was also incorporated into the study. Physicochemical properties were assayed using standard methods, mineral analysis by ICP-OES, phenolic compound assay by the Folin Ciocalteau method, antioxidant activity by DPPH radical scavenging ability, antimicrobial activity by the disc diffusion method and bioaccessibility was assayed using the Infogest digestion protocol. Sensory evaluation was also done to gauge the acceptance of the enzyme macerated samples. The physicochemical properties of the enzyme macerated juice and enzyme porridge were more appreciable compared to their nonenzyme counterparts. The mineral content was highest in the pulp (9.12 mg/100g for iron and 2.04 mg/100g for zinc) followed by enzyme macerated juice (8.89 mg/100g for iron and 2 mg/100g for zinc). The enzyme porridge also recorded higher levels of mineral content. Vitamin C content was affected by the thermal processing used in juice extraction and porridge preparation, although the enzyme juice still contained appreciable vitamin C content (9.45 mg/100g). The total phenol content was also higher in the enzyme juice with recorded value of 3327.75 mg/100g. The same trend was observed for antioxidant and antimicrobial activities with the enzyme macerated juice recording higher results (76.4 % for DPPH radical scavenging AOA). The bioaccessibility of iron, zinc, ascorbic acid and total phenolic compounds was higher in the enzyme treated samples, with values of 28.76 %, 18.14 %, 37.89 % and 36.75 % respectively in enzyme macerated juice. The bioaccessibility of micronutrients was significantly lower (p < 0.05) in the porridge samples, clearly highlighting the effect of the food matrix in determining bioaccessibility. The enzyme macerated samples had higher acceptance on sensory evaluation. The observed results in this study are mostly attributable to the breakdown of the complex polysaccharide, pectin, into simpler more volatile compounds such as galacturonic acid. From the observed results it can be concluded that enzyme macerated S. cocculoides juice is an excellent source of some bioaccessible micronutrients and phenolic compounds; hence its consumption should be encouraged especially in nutrition-related intervention programmes. However further research is still needed to identify individual specific phenolic compounds in S. cocculoides juice and how they are affected by enzyme maceration and in-vitro digestion. The work done in this study can also be employed for other indigenous fruits to promote their utilisation and increase their value.